Moving vehicle recognition and classification based on time domain approach - Paulraj, Murugesa Pandiyan, Prof. Dr.; Abd Hamid, Adom, Prof. Dr.; Sathishkumar, Sundararaj; Norasmadi, Abdul Rahim (Elsevier Ltd, 2013)
Link to publisher's homepage at http://www.elsevier.com/